Regional stability and adaptation measures slope failures due to rainfall in Singapore - Chan, Claire Yi En (2022)
As heavier rainfall intensities are expected in the future, it is important to employ preventive measures for the anticipated possibility of residual soil slope failures. This study primarily focuses on the principles of unsaturated soil mechanics to establish an appropriate framework for adaptation measures against extreme rainfall conditions. These adaptation measures consist of the development and evaluation of slope susceptibility maps, as well as the planting of vegetation for critical slopes based on regional stability analyses of residual soils within Bukit Timah Granite and Old Alluvium in Singapore. In this study, slope susceptibility maps were developed for three zones of residual soils within Bukit Timah Granite and Old Alluvium in Singapore. The pore-water pressure distributions and factors of safety within each zone were obtained from the Transient Rainfall Infiltration and Grid-based Regional Slope-stability model (TRIGRS) analysis and Scoops3D software, respectively. Results from the slope susceptibility maps were verified against two-dimensional (2D) numerical analyses. The 2D numerical models were verified through instrumentation data. The results from slope susceptibility maps agreed with the results from 2D numerical analyses. In addition, the inclusion of vegetation at the slope face was concluded to be an effective slope stabilisation measure from the simulated 2D numerical analyses.